Knowledge and awareness of aetiological and risk factors as determinants of health-seeking pattern of parents of children with epistaxis in a tertiary health institution: A 7-year prospective study - Shuaib Kayode Aremu (Wolters Kluwer Medknow Publications, 2023)
Aim: This prospective study aimed to assess the knowledge and awareness of aetiological and risk factors as determinants of the health-seeking pattern of parents of children with epistaxis in a tertiary health institution. Materials and Methods: This was a 7-year cross-sectional prospective study where copies of the questionnaire were distributed to consenting parents whose children presented to our institution with epistaxis between January 2015 and December 2021. A total of 570 parents were enrolled in the study in the research time period. Results: Out of 570 patients, majority (39%) were aged between 11 and 15 years, followed by 35% aged between 6 and 10 years, 17% aged between 1 and 5 years and 11% aged between 16 and 18 years. Three hundred and eighty (66.67%) were male and 190 (33.33%) were female. Two hundred and ninety-five (51.75%) patients had primary education, followed by 189 (33.16%) patients with secondary education and 86 (15.09%) patients with preschool education. Three hundred and seventy-three (65.44%) patients had anterior bleeding and 107 (18.77%) patients had posterior bleeding while 90 (15.79%) patients had both anterior and posterior bleeding. The majority of the parents, 399 (70%), were aware about the epistaxis while 171 (30%) parents were unaware about the epistaxis. Conclusion: A significant number of parents are unaware of the epistaxis and also unaware of the various aetiological and risk factors of the epistaxis and these issues need a more nuanced analysis in light of Africa's rich cultural diversity.